The economic costs of Alzheimer's disease. - Hay, J W (1987)
This paper estimates the economic costs of Alzheimer's Disease to individuals and to society, based on review of published Alzheimer's Disease-related research. The analysis is derived from epidemiological projections and cost information for the United States population in 1983. Estimated costs include both direct medical care and social support costs, as well as indirect costs, such as support services provided by family or volunteers, and the value of lost economic productivity in Alzheimer's Disease patients. Mid-range estimates of net annual expected costs for an Alzheimer's Disease patient, excluding the value of lost productivity, are $18,517 in the first year and $17,643 in subsequent years, with direct medical and social services comprising about half of these costs. Under base case assumptions, the total cost of disease per patient in 1983, was $48,544 to $493,277, depending upon patient's age at disease onset. The estimated present value of total net costs to society for all persons first diagnosed with Alzheimer's Disease in 1983 was $27.9-31.2 billion. Development of a public or private insurance market for the economic burdens of Alzheimer's Disease would fill some of the gaps in the current US system of financing long-term chronic disease care.